The Presbyterians in Colombia (1856-1993): A Historical Look through their Worship, Liturgy and Temples - Ramírez Suárez, Luis Eduardo (2021)
This article explores, through a historical view of worship, liturgy, and temples, how the Presbyterian Church was established and contextualized to Colombia, facing symbolic struggles in an environment of confrontation and differentiation, first with the Catholic Church and then with the theological movements within the Protestant world, from its establishment in the mid-19th century to its consolidation in the 20th century. This exploration takes place through bibliographic and documentary research, and an analysis of the development of worship, liturgy and temples, allowing us to glimpse the changes and permanence in the imaginaries, representations and practices that materialized in the church’s institutions and discourses, and that impacted all the spheres of its reality. These changes were the product of the hermeneutical work of reading the Bible to make it relevant to its context.